Quest for participatory democracy: towards understanding the approach of Gandhi and Jayaprakash Narayan - Anand Kumar (ed.); Manish Tiwari (ed.) (Jaipur : Rawat Publications, 2010)
Contributed articles presented at an international seminar organized by Jawaharlal Nehru University, New Delhi; with reference to India.
Keywords: Democracy India; Political Science; Social Sciences